BABUR'S WORK AS A PHILOSOPHY OF ETHICS AND LOVE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In this article, the author analyzed and described the sociocultural and scientific environment of Transoxiana and India in the 16th-17th centuries. The reasons for the stability and prosperity of the Mughal state, and the collapse of the empire. The author identifies the factors for the remarkable growth of the culture of the Mughal Empire.